Spatial and temporal patterns of modern ( 100 yr) sedimentation in a tidal freshwater marsh: Implications for future sustainability. (28th September 2015) - Palinkas, Cindy M.; Engelhardt, Katharina A. M.
Abstract: To maintain their position within the tidal frame, tidal marshes must accrete upward at approximately the same rate as relative sea‐level rise (RSLR), typically accomplished through accumulation of mineral (from fluvial, estuarine, and/or coastal waters) and/or organic (plant‐derived) sediments. However, accelerating RSLR and declining fluvial suspended‐sediment supplies, along with other direct anthropogenic disturbances, may limit the ability of many marshes to keep pace. This study tests hypotheses addressing the relationship of marsh surface elevation and channel influence to marsh accretion and evaluating marsh response to historic mining disturbance and long‐term environmental change, using Dyke Marsh Preserve, a tidal freshwater marsh located along the Potomac River estuary (Chesapeake Bay watershed) as a model system. Variability in sediment characteristics (grain size, organic content, bulk density) and decadal‐scale accretion rates (using 210 Pb) across the marsh platform is related to ecogeomorphic setting, anthropogenic activities (mining), and long‐term changes in river sediment supply and RSLR. In general, sediment on river/tidal‐channel banks accumulates faster and is more influenced by fluvially derived sediment than in the marsh interior. Accumulation rates on the banks can be predicted using proxies for sediment supply and availability most of the time; however, these relationships do not hold for the marsh interior, highlighting the role of sediment redistribution and/or complex sediment‐vegetation interactions. Development of temporally variable sediment rating curves reveals that suspended‐sediment loads of the Potomac River have decreased since the late 1970s, although current loads appear adequate to support accretion on the marsh platform, if net onshore sediment‐transport mechanisms exist.